KOMISJA EDUKACJI NARODOWEJ A ENCYKLOPEDIA, ALBO SŁOWNIK ROZUMOWANY NAUK, SZTUK I RZEMIOSŁ (CZ. 2. WYMIAR DYDAKTYCZNY) - Janeczek, Stanisław (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
This paper combines on the one hand the educational ideals and didactics in the schools of the Polish–Lithuanian Commonwealth reformed by the Commission of National Education (1773), and on the other hand one of the most representative testimonies of the then intellectual culture, i.e. Encyclopédie ou dictionnaire universel raisonné des sciences, des arts et des métiers, published in the years 1751–1780. It shows continuity with regard to learned culture and the place of philosophy in modern school. In accord with the standards of the Encyclopédie the European school preserved the course of philosophy in the spirit of philosophia recentiorum, at least at the university level. This philosophy took a critical approach in its assimilation of the elements of modern epistemology, especially the accomplishments of modern natural sciences. Such attitude was also typical of the school reformed in the mid-eighteenth century in the Commonwealth, especially by the orders of Piarists and Jesuits. The Commission had introduced independent mathematical and natural subjects, a fact that limited philosophy. In secondary schools philosophy was reduced to logic and practical ethics, and at universities to natural law with social, political, and economic elements. For this reason they even departed from a traditional structure of university, with a propedeuctic faculty of philosophy, when in the spirit of the physiocratic physical and moral orders a two-element structure of universities was established. Despite these changes, philosophical elements can be found even in the didactics of natural sciences in the schools of the Commission. The same tendencies are apparent in the then European school, therefore in the form of interpretations drawing on the category of substance and its properties, or even the conception of the animal soul.